Replication Data for "The Gendered Impacts of Income Fluctuations on Household Departure, Labor Supply, and Human Capital Decisions" - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
These files consist of the do-files and data for reproducing results presented in the article, ""The Gendered Impacts of Income Fluctuations on Household Departure, Labor Supply, and Human Capital Decisions"" (Kosec et al., 2021). The data files were constructed from Kyrgyz Integrated Household Survey (KIHS) spanning from 2004 to 2016. KIHS is a nationally-representative, multi-topic rotating panel household survey conducted quarterly since during 2003-2016.The primary respondent is the household head or a knowledgeable member, who completed a household roster and employment module covering individuals aged 15?65, among other modules. Each year up to 2013, up to 25 percent of households exited the sample; in 2013, an entirely new sample was selected. There are on average three observations per household each year, and the median household is in the sample for four years. In total data from 164,997 individuals from 14934 households were used for the analysis.